The Driving Force of the Na+/Ca2+-Exchanger during Metabolic Inhibition - Baartscheer, Antonius; Schumacher, Cees A.; Coronel, Ruben; Fiolet, Jan W. (Frontiers in Physiology, 2011)
Objective Metabolic inhibition causes a decline in mechanical performance and, if prolonged, myocardial contracture and cell death. The decline in mechanical performance is mainly due to altered intracellular calcium handling, which is under control of the Na+/Ca2+-exchanger (NCX) The driving force of the Na+/Ca2+-exchanger (DGncx) determines the activity of NCX. The aim of this study was to describe the relation between DGncx and calcium homeostasis during metabolic inhibition. Methods In left ventricular rabbit myocytes, during metabolic inhibition (2 mM sodiumcyanide), sodium ([Na+]i), calcium ([Ca2+]i) and action potentials were determined with SBFI, indo-1 and the patch clamp technique. Changes of dGncx were calculated. Results During metabolic inhibition: The first 8 minutes [Na+]i remained constant, systolic calcium decreased from 532±28 to 82±13 nM, diastolic calcium decreased from 121±12 to 36±10 nM and the sarcoplasmic reticulum (SR) calcium content was depleted for 85±3%. After 8 minutes [Na+]i and diastolic calcium started to increase to 30±1.3 mM and 500±31 nM after 30 minutes respectively. The action potential duration shortened biphasically. In the first 5 minutes it shortened from 225±12 to 153±11 ms and remained almost constant until it shortened again after 10 minutes. After 14 minutes action potential and calcium transients disappeared due to unexcitability of the myocytes. This resulted in an increased of the time average of dGncx from 6.2±0.2 to 7.7±0.3 kJ/mol during the first 3 minutes, where after it decreased and became negative after about 15 minutes. Conclusions Metabolic inhibition caused an early increase of Gncx caused by shortening of the action potential. The increase of dGncx contributed to decrease of diastolic calcium, calcium transient amplitude, SR calcium content and contractility. The increase of diastolic calcium started after dGncx became lower than under aerobic conditions.